Revitalizing the Classical Waqf Model for Contemporary Higher Education: Lessons from Fatimah al-Fihri, Morocco - Sulistyowati Sulistyowati; Holifurrahman Holifurrahman; Ahmad Zubaidi (Badan Wakaf Indonesia, 2026)
Waqf has historically played a pivotal role in the development of education in the Muslim world. This study revisits the classical model of educational waqf through the legacy of Fatimah al-Fihri, the founder of Al-Qarawiyyin University in 859 CE in Fez, Morocco.— widely recognized as the world’s first higher learning institution funded entirely through waqf. Using a descriptive qualitative approach, the research analyzes historical texts, institutional records, and classical Islamic legal sources to trace how educational waqf emerged as a sustainable model for intellectual development, social mobility, and knowledge dissemination. The study finds that the classical waqf model was deeply integrated into the structure of Muslim societies, enabling the establishment of universities, libraries, teacher salaries, and student support systems — independent from state control. The novelty of this research lies in its critical reflection on how these early models can inform contemporary practices in revitalizing waqf-based educational systems, particularly in Muslim-majority countries like Indonesia. By extracting institutional design principles from the classical period — such as autonomy, community involvement, and long-term vision — this study proposes a framework for reimagining educational endowments as strategic tools for national development. The findings suggest that reviving the classical spirit of waqf is not merely about preserving heritage, but about transforming education into a self-sustaining, inclusive, and faith-driven system. This research contributes to ongoing debates on Islamic philanthropy, higher education reform, and the role of religious endowments in modern socio-economic development.